Real-world evidence of autoimmune hepatitis following COVID-19 vaccination: A population-based pharmacovigilance analysis - Chen, Congqin; Xie, Danfei; Xiao, Jie (Frontiers in Pharmacology, 2023)
Objective: Autoimmune hepatitis (AIH) has occasionally been reported after administration of Coronavirus Disease 2019 (COVID-19) vaccine. The present study aimed to investigate the reporting rate and disproportionality of AIH following COVID-19 vaccination. Methods: The Centers for Disease Control (CDC) COVID Data Tracker and the Vaccines Adverse Event Reporting System (VAERS) were queried between December 11, 2020 and March 15, 2022. Reported rates were calculated by cases of AIH divided by the number of vaccinated people. Disproportionate pattern of AIH for COVID-19 vaccination was accessed based on the reporting odds ratio and empirical bayes geometric mean (ROR and EBGM, respectively). Results: A total of 53 reports of AIH were identified after administration of COVID-19 vaccine during the study period. The overall reported rate of COVID-19 vaccination-related AIH was 0.21 (95% CI 0.16-0.27) per million people. The results found no disproportionate reporting of AIH following COVID-19 vaccination in the VAERS (overall: ROR 1.43, 95% CI 0.52–3.96; EBGM05 0.37. mRNA: ROR 1.42, 95% CI 0.51–3.94; EBGM05 0.37. Virus vector: ROR 1.57, 95% CI 0.42–5.85; EBGM05 0.34). Conclusion: COVID-19 vaccine did not increase the risk of AIH. The number of AIH cases reported to VAERS does not suggest a safety concern attributable to COVID-19 vaccine at this time.